1999
DOI: 10.2337/diacare.22.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous oxygen tension and toe blood pressure as predictors for outcome of diabetic foot ulcers.

Abstract: The results indicate that TcPO2 is a better predictor for ulcer healing than TBP in diabetic patients with chronic foot ulcers, and that the probability of ulcer healing is low when TcPO2 is < 25 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
198
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(210 citation statements)
references
References 0 publications
4
198
0
8
Order By: Relevance
“…TcPO 2 , being a composite measure of several factors such as arterial pressure, arterial oxygen content, local tissue perfusion pressures, neurovascular function and local oxygen consumption, may be a more relevant measure, as it seems to reflect micro-as well as macrocirculation. TcPO 2 has previously been shown to be related to outcome in diabetic foot ulcers [7]. Case series indicate that TcPO 2 might be a predictor for healing after HBOT, but large comparative studies are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…TcPO 2 , being a composite measure of several factors such as arterial pressure, arterial oxygen content, local tissue perfusion pressures, neurovascular function and local oxygen consumption, may be a more relevant measure, as it seems to reflect micro-as well as macrocirculation. TcPO 2 has previously been shown to be related to outcome in diabetic foot ulcers [7]. Case series indicate that TcPO 2 might be a predictor for healing after HBOT, but large comparative studies are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…TcPO 2 measurements were performed at the dorsum of the foot, with the patients initially in a supine and then in a sitting position with their legs hanging down for postural provocation. The reference value was determined by placing the probe on the right side of the chest in the suclavian region and calculating the regional perfusion index (16). To further exclude peripheral vascular disease or mediasclerosis as potential sources of error, the ankle pressures were measured with a 10-cm-wide pneumatic cuff and a Doppler flow probe (Huntleigh Diagnostics, Cardiff, U.K.).…”
Section: Skin Blood Flow Determinationmentioning
confidence: 99%
“…The healing prediction index exhibited a sensitivity and specificity of 80 and 74%, respectively. 31 Alternatively, Kalani et al 54 measured the transcutaneous oxygen tension (TcPO 2 ) on the feet of 50 type 1 and 2 diabetes patients with existing diabetic foot ulcers. They showed that the ulcers on the feet of patients with TcPO 2 greater than 25 mm Hg healed within 4-6 weeks while ulcers on the feet of patients with TcPO 2 lower than 25 mmHg did not heal.…”
mentioning
confidence: 99%
“…The sensitivity and specificity of the ulcer healing prediction index obtained using hyperspectral imaging 31,32 were lower than those reported for TcPO 2 . 54 However, hyperspectral imaging is noninvasive and can assess oxygen saturation with high spatial resolution in a relatively short time. On the contrary, TcPO 2 requires (1) physical contact between the foot and a probe, (2) can only measure the average tissue oxygen content over an entire limb, and (3) may take up to 20 minutes to produce a reading.…”
mentioning
confidence: 99%